Climate change and social learning (CCSL): supporting local decision making for climate change, agriculture and food security - Carlile, Liz; Ballantyne, Peter G.; Ensor, Jonathan; Förch, Wiebke; Garside, Ben; Harvey, Blane; Patterson, Zachary; Thornton, Philip K.; Woodend, John (2013)
The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS1) is challenging its own community of scientists and partners to understand the importance of co-created knowledge in finding solutions to local climate change issues. Local communities dealing with the daily realities of climate change risk, adaptation and mitigation don’t have time to wait. They need an immediate way to combine their own knowledge with that of others to build better solutions. CCAFS believes it can use the concept of social learning to challenge the CGIAR family and others to adopt new ways of working, forge new partnerships and co-create new knowledge to support more collective local decision making on climate change.